A CASE STUDY ON LAW AND HEALTH WITH SPECIAL REFERENCE TO INTERNET GAMING DISORDER - Satyam, Sourabh (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The intersection of law and health is becoming increasingly significant with the rise of digital disorders like Internet Gaming Disorder (IGD). This study explores the legal frameworks and public health strategies addressing IGD. The research highlights the global recognition of IGD by organizations like the World Health Organization (WHO), the evolving legal responses to regulate gaming behavior, and the societal impacts of this condition. This study aims to assess the adequacy of existing laws, identify gaps, and propose actionable solutions to mitigate the disorder’s impact on individuals and society.